The taming of the Canaanite woman : constructions of Christian identity in the afterlife of Matthew 15:21-28 - Klancher, Nancy (Berlin : De Gruyter, 2013)
Current reception histories emphasize the world of Biblical readers, their socio-historical contexts, and the myriad effects of Biblical exegesis. This reception history studies interpretations of Jesus' encounter with a Canaanite woman (Matt 15:21-28) as normative "scripts" that exhort specific types of compliance in a broad range of historical and cultural settings, revealing remarkably diverse understandings of Christian identity and community.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed December 24, 2013).
Keywords: Bible. -- Criticism, interpretation, etc; Theology; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; Electronic books